Réponses

2012-10-09T21:13:37+02:00

(2*x+3)/(1-x)<=(-3*x-22)/(3*x-2)
il faut x différent de 1 et 2/3

(2x+3)(3x-2) <= (-3x-22)(1-x)
6x² - 4x + 9x - 6 <= -3x + 3x² - 22 + 22x
6x² + 5x - 6 + 3x - 3x² + 22 - 22x <= 0
3x² - 14x + 16 <= 0

3(x² - 14x/3 + 16/3) <= 0
x² - 14x/3 + 16/3 <= 0

début en :
(x - 7/3)² = x² - 14x/3 + 49/9

(x - 7/3)² - 49/9 + 16/3 <= 0
(x - 7/3)² - 49/9 + 48/9 <= 0
(x - 7/3)² - 1/9 <= 0

(x - 7/3)² - (1/3)² <= 0
(x-7/3-1/3)(x-7/3+1/3) <= 0
(x-8/3)(x-2) <= 0

puis tableau de variation...

donc x appartient à ]-oo ; 2/3 [ U ]1;2] U [8/3; +oo[

En espérant t'avoir aidé.